DEVELOPMENT OF PROFESSIONAL COMPETENCY OF TEACHERS AS THE MAINTENANCE OF ACADEMIC GOODWILL - Bobkova, Antonіna; Melnychuk, Оleh; Melnychuk, Olha; Melnychuk, Maksym; Pypiak, Mykola (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The purpose of the article is to reveal the direct influence of research and teaching staff professional competence on their academic integrity. The authors used theoretical and empirical research methods to validate the results. The use of the dialectic method made it possible to show a close link between teachers’ professional competence development and their adherence to academic integrity. By means of the comparative method we managed to reflect the scientists to the academic dishonesty in Ukraine and abroad. The researchempirical basis is the results of a survey of 250 teachers of higher education institutions in Vinnitsa region, including Vinnytsia State Pedagogical University named after Mykhailo Kotsiubynskyi, Vinnytsia Trade and Economic Institute of Kyiv National University of Trade and Economics and Donetsk National University named after Vasyl Stus. In addition, the authors’ own experience of scientific and pedagogical work of the authors of this article was taken into account.The requirement of the legislator is to adhere by the scientific and pedagogical staff of academic virtue that can be realized through the development of motivational-value, cognitive-operational, reflexive-evaluation components of the teacher's professional competence. Scientific and pedagogical staff should systematically form professional knowledge, skills, personal traits that would ensure academic integrity.